Altslawische Kultstrukturen in Pohansko bei Břeclav (Tschechische Republik) - Macháček, Jiři (Studia mythologica Slavica, 2000)
This piece discusses the first stages of research, conducted with the aid of metric analysis, on the ancient Slavic site of Pohansko near the city of Břeclav in the south-east region of the Czech Republic. This analysis includes two pagan sanctuaries, grave sites, an early medieval church, dwelling structures and defense ramparts. A unified system of orientation is determined, dependant on the calendar direction of the solstice rising and setting of the sun and moon and the course of the defense ramparts was also established in this fashion.
Keywords: Slavs; Slovani; mitologija; mythology; Pohansko (Břeclav); gradišča; svetišča; arheološke najdbe; kulti; archaeology; arheologija